Determination of Genotoxicity Attributed to Diesel Exhaust Particles in Normal Human Embryonic Lung Cell (WI-38) Line - Joong Won Lee; Hee Jae Lee; Young-Joo Lee; Yong-beom Lim; Woo Jong Sim; Ji-Hye Jang; Hye-Ryeon Heo; Hyun Joung Lim; Ji-Won Jung; Jin Sik Kim (Biomolecules, 2021)
Several epidemiological studies concluded that inhalation of diesel exhaust particles (DEP) is associated with an increase in the relative risk of lung cancer. In vitro research evaluating the genetic damage and/or changes in gene expression have been attempted to explain the relationship between DEP exposure and carcinogenicity. However, to date, investigations have been largely confined to studies in immortalized or tumorigenic epithelial cell models. Few studies have investigated damage at the chromosomal level to DEP exposure in normal cell lines. Here, we present the genotoxic effects of DEP in normal cells (embryonic human lung fibroblasts) by conventional genotoxicity testing (micronuclei (MN) and comet assay). We show the differentially expressed genes and enriched pathways in DEP-exposed WI-38 cells using RNA sequencing data. We observed a significant increase in single-strand DNA breaks and the frequency of MN in DEP-exposed cells in a dose-dependent manner. The differentially expressed genes following DEP exposure were significantly enriched in the pathway for responding to xenobiotics and DNA damage. Taken together, these results show that DEP exposure induced DNA damage at the chromosomal level in normal human lung cells and provide information on the expression of genes associated with genotoxic stress.